1999
DOI: 10.1080/09603129973164
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of water vending machines

Abstract: Consumption of water from vending machines has recently increased in the United States. However, studies describing the bacteriological quality of water from these machines are scarce. In this study, bacteriological analyses were performed on samples from 30 water vending machines (W VM s), three of which were sampled weekly for 3 weeks. Bacteriological analyses were also conducted on the nozzle dispensers and the drains of 15 WVMs. Heterotrophic bacteria, total and fecal coliforms, and Pseudomonas aeruginosa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
1
9
0
3
Order By: Relevance
“…Despite cases of water vending machines contaminated by faecal coliforms (E. coli O157:H7) [50] , fortunately, none of the selected subjects in this study was found to harbour faecal coliform (Figure 1, Table 3). However, in accordance to other studies [51,52] ,the presence of other total coliform (eg. Klebsiella, Enterobacter or Citrobacter species) was reported in our findings.…”
Section: Bacterial Colonies On Hicrome Tm Coliform Agarssupporting
confidence: 92%
“…Despite cases of water vending machines contaminated by faecal coliforms (E. coli O157:H7) [50] , fortunately, none of the selected subjects in this study was found to harbour faecal coliform (Figure 1, Table 3). However, in accordance to other studies [51,52] ,the presence of other total coliform (eg. Klebsiella, Enterobacter or Citrobacter species) was reported in our findings.…”
Section: Bacterial Colonies On Hicrome Tm Coliform Agarssupporting
confidence: 92%
“…In total, 16 out of 49 samples which are 32% of the overall results detected total coliform. A quite similar study detected coliform bacteria in 20% of the drinking water samples from vending machines [5]. The microbial contamination can be mainly from soil/dust or due to the presence of some insects, but most of the bacteria belonging to the total coliform group do not cause serious health effects since they are considered harmless [8], [9].…”
Section: Resultsmentioning
confidence: 84%
“…The presence of this bacterium mainly indicates low nutrient environment, as it lives in soils, water, and hot or moisture environment [6]- [8]. It causes many side effects, especially to the immuno-compromised people who are already weak and responsible for the common outbreaks and infections such as respiratory system infections, urinary tract infections, and various types of systematic infections [5].…”
Section: Resultsmentioning
confidence: 99%
“…Technology has allowed vended water to evolve even further in the developed world, and a recent body of literature highlights the challenges in maintaining quality control of machine-vended water (i.e. filling personal containers) in the US and Europe (McSwane et al 1994; Chaidez et al 1999; Hunter & Barrell 1999; Schillinger & Du Vall Knorr 2004). The vast majority of published literature on sachet water addresses product quality, and this section reviews that body of work.…”
Section: Sachet Water Qualitymentioning
confidence: 99%